Ghana Keta Groundwater Games for Resource Governance - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The study intervention included playing an irrigation groundwater governance game with multiple rounds and treatments in each village: one game with 5 men players and one game with 5 women players. Player choices and group outcomes (including water withdrawals and availability) for each round of the game were recorded and uploaded to SurveyCTO. A pre- and post-game survey of individual players immediately before and immediately after the game was conducted to gather data on characteristics of the players, their households and farms including current irrigation practices, individual mental models regarding groundwater resources and their management, and perceptions about levels of trust and cooperation between community members. The games and surveys were conducted in 10 villages within 2 districts of the coastal Keta basin of Ghana (located in the Volta Region of Ghana).